Plasma mitochondrial DNA levels were independently associated with lung injury in elderly hip fracture patients. Issue 2 (February 2017) - Zhang, Jian-zheng; Wang, Juan; Qu, Wen-chun; Wang, Xiao-wei; Liu, Zhi; Ren, Ji-xin; Han, Li; Sun, Tian-sheng
Abstract: Introduction: Hip fracture in the elderly can induce systemic inflammatory response (SIRS) and lung injury which increases the risk of lung infection and death. Mitochondrial DNA (mtDNA) plays a role in SIRS and lung injury in patients with multi-trauma, and also in patients with hip fractures. This study evaluated the potential value of plasma mtDNA in the early prognosis of lung injury in elderly fracture patients. Methods: This study enrolled 156 elderly patients with intertrochanteric fracture. Plasma mtDNA, IL-6, IL-10, prostaglandin E2 (PGE2) levels were measured at admission. Sixty-one and 31 patients were diagnosed with systemic inflammatory response syndrome (SIRS) and lung injury, respectively. Results: Plasma mtDNA levels were higher in hip fracture patients compared to healthy controls (P < 0.001) and significantly higher in the lung injury subgroup compared to the lung injury absent subgroup (P < 0.001). MtDNA levels were correlated with the SIRS score (r = 0.446, P < 0.001), IL-6 (r = 0.506, P < 0.001), IL-10 (r = 0.523, P < 0.001), and PGE2 (r = 0.360, P < 0.001). Logistic regression analysis revealed that plasma mtDNA, IL-6, PGE2 and SIRS score were independent predictors of the risk of lung injury. Conclusion: Plasma mtDNA release induced by hip fracture in elderly patients, might be an early predictor of lung injury in these patients.